The Phenomenon of Staff Attrition in Sri Lanka’s Hospitality Industry - Galagoda, Emadhrie Arundanie (2016)
Sri Lankan Hospitality Industry has just commenced to emerge as a mainstream socio-economic sector, with acknowledgement of its job-creating significance. Undeniably, in recent times the Sri Lanka hotel industry is challenged with a comparatively high attrition rate fueled by a dearth of hospitality manpower in the imminent future. This study aims to fulfill an unidentified study on the phenomena of staff attrition, the dominant antecedents underlying an employee’s intention to exit the industry and an exploration of the realities or nature of the industry. Using a Qualitative research methodology approach, the study sought invaluable insights from hospitality industry experts and hoteliers from individual hotels to apprehend the authenticities of the phenomenon. The results revealed the predicament stemming from the bottom-rung of the employment chain with Economic factors such as; a lower compensation package and perceived alternative opportunities portraying as the key antecedents to have triggered the inception of attrition in the industry. Besides, organizational and personal factors were revealed to be supplementary antecedents. The study concludes by offering some unique recommendations to HR strategists and industry experts which would be beneficial in mitigating the phenomenon of staff attrition in the future.